DESIGN AND PERFORMANCE EVALUATION OF AN AFFORDABLE DATA ACQUISITION SYSTEM FOR REAL-TIME SPERLING RIDE INDEX ASSESSMENT - Hafizh Dwilyadi, Naufal
In rail transportation, one of the important parameters to assess is the Sperling ride index. This index rates the ride quality based on the vibration of the train’s cabin. However, current measurement of the ride index is conducted using general vibration measuring instruments. As a result, the ride index measurement is not in real-time and it requires a separate time for data processing. Therefore, in this research, a data acquisition system will be built for measuring the Sperling ride index that can also display the measurement results in real-time. The design process begins with determining the design requirements and objectives. Based on the established design requirements and objectives, the data acquisition system’s hardware is built which consists of a vibration sensor, the ADXL355, and a microcontroller, the ESP32. Next, a program is created that functions to record, process, and display the measurement data. This program was created based on the Matlab and the Arduino IDE software. At the end of the research, a performance test of the data acquisition system is conducted. The results of the performance test show that the device made has met the design requirements. This device has an error within ±5% for vibrations with frequencies below 68 Hz; whereas, the resulting peak-to-peak noise value is found to be 2 m????. Aside from that, the experimental results show that the program can display the Sperling ride index in real-time, then send the results automatically to the observer’s smartphone via email.